2020
DOI: 10.1136/svn-2020-000664
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of 10K patients with acute ischaemic stroke or transient ischaemic attack: design, methods and baseline patient characteristics

Abstract: Background and purposeStroke is the second leading cause of death worldwide and the leading cause of mortality and long-term disability in China, but its underlying risk genes and pathways are far from being comprehensively understood. We here describe the design and methods of whole genome sequencing (WGS) for 10 914 patients with acute ischaemic stroke or transient ischaemic attack from the Third China National Stroke Registry (CNSR-III).MethodsBaseline clinical characteristics of the included patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 77 publications
(68 reference statements)
0
33
0
Order By: Relevance
“…Both ischemic and hemorrhagic [ 109 ] strokes have been observed in patients with COVID-19 and are more likely to be seen in individuals experiencing a more severe course of disease, with cardiovascular disease (CVD) risk factors (e.g., hypertension, diabetes, and history of CVD), increased inflammatory response, and hypercoagulable state (as reflected in CRP and D-dimer levels) [ 99 , 100 , 110 ]. A cohort study in the NYU Langone Health system noted a mean age of 61.6 years for COVID-19-positive patients with intracranial hemorrhage [ 109 ], and a systematic review found a mean age of 63.4 for acute ischemic stroke [ 111 ].…”
Section: Acute Cns Symptoms In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Both ischemic and hemorrhagic [ 109 ] strokes have been observed in patients with COVID-19 and are more likely to be seen in individuals experiencing a more severe course of disease, with cardiovascular disease (CVD) risk factors (e.g., hypertension, diabetes, and history of CVD), increased inflammatory response, and hypercoagulable state (as reflected in CRP and D-dimer levels) [ 99 , 100 , 110 ]. A cohort study in the NYU Langone Health system noted a mean age of 61.6 years for COVID-19-positive patients with intracranial hemorrhage [ 109 ], and a systematic review found a mean age of 63.4 for acute ischemic stroke [ 111 ].…”
Section: Acute Cns Symptoms In Covid-19mentioning
confidence: 99%
“…The occurrence of ischemic strokes [ 99 , 100 , 110 ] as well as the predominance of vascular neuropathlogic findings (i.e., microthrombi, acute infarction) found in autopsies [ 77 ] of individuals with COVID-19 are significant causes of concern for potential morbidity and mortality. This leads to the question—are there hemostatic abnormalities induced in SARS-CoV-2 infection?…”
Section: Acute Clotting Disorders In Covid-19mentioning
confidence: 99%
“…[ 11 ] Among the 219 COVID-19 patients, COVID-19 patients with cerebrovascular disease are significantly older, are more likely to develop into severe COVID-19 and may have cardiovascular risk factors, including a history of hypertension and diabetes. [ 102 ] In a case study of SARS-CoV-2 infection, there were more male patients than females. In addition, about half of infected patients suffered from chronic underlying diseases, mainly cardiovascular and cerebrovascular diseases and diabetes.…”
Section: Endothelial Dysfunction: a Collision Of Thromboinflammation Cytokine Storm And Ace2 Downregulationmentioning
confidence: 99%
“…Monocyte activation is postulated to constitute part of the secondary hemophagocytic lymphohistiocytosis described in severe COVID-19 [ 41 ]. Thrombocytopenia with elevated d -dimer and C-reactive protein in severe COVID-19 and stroke is consistent with a virus-associated microangiopathic process [ 42 ]. Higher production of anti-cardiolipin and anti-β2GP1 antibodies has been also reported in patients with COVID-19 [ 43 ].…”
Section: Sars‐cov‐2: Neurovirulence and Central Nervous System Entry Routesmentioning
confidence: 99%